2021
DOI: 10.3389/fimmu.2021.800879
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor-Associated Colitis: From Mechanism to Management

Abstract: Immune checkpoint inhibitors (ICIs), as one of the innovative types of immunotherapies, including programmed cell death-1 (PD-1), programmed cell death-ligand 1 (PD-L1), and cytotoxic T lymphocyte antigen 4 (CTLA-4) inhibitors, have obtained unprecedented benefit in multiple malignancies. However, the immune response activation in the body organs could arise immune-related adverse events (irAEs). Checkpoint inhibitor colitis (CIC) is the most widely reported irAEs. However, some obscure problems, such as the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 244 publications
(359 reference statements)
0
78
0
1
Order By: Relevance
“…Furthermore, another controversial issue is gut toxicity from previous chemotherapy and radiotherapy, and their effect on the risk profile for ICI-induced colitis. Studies carried out on lung cancer patients who received ICI with previous chemotherapy and radiotherapy did not show an increased risk of ICI colitis [16]. However, the sample sizes of these studies were small.…”
Section: Risk Factorsmentioning
confidence: 88%
“…Furthermore, another controversial issue is gut toxicity from previous chemotherapy and radiotherapy, and their effect on the risk profile for ICI-induced colitis. Studies carried out on lung cancer patients who received ICI with previous chemotherapy and radiotherapy did not show an increased risk of ICI colitis [16]. However, the sample sizes of these studies were small.…”
Section: Risk Factorsmentioning
confidence: 88%
“…Immune system homeostasis is substantially altered when the actions of CTLA-4 and PD-(L)1 are inhibited, causing a subsequent increase in T-cell and innate lymphoid cell activity. These alterations have a particularly strong effect on the intestinal mucosa, where they initiate an in ammatory cascade that can profoundly damage the gut lining (Tang 2021). Differentiating between post-ICI-colitis episodes that are exacerbations of pre-existing MC from those that indicate new, ICI-induced colitis that differs from MC is very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome is quickly becoming an area of increased interest for multiple GI conditions (e.g., C. di cile colitis and in ammatory bowel diseases) regarding pathogenesis and treatment, typically among clinicians treating patients in whom standard-of-care treatments have been ineffective. Several theories on the mechanism of the microbiome-immune system interface posit that ICIs cause intraepithelial lymphocyte-mediated apoptosis of the intestinal epithelium, which consequently disrupts the intestinal mucosa barrier and allows for potential innate immune system activation when immune cells encounter the gut microbiome (Tang et al 2021). Interestingly, Chaput et al observed that speci c gut microbiome compositions are associated with a higher likelihood of developing ICI colitis but more favorable responses to ICI therapy with ipilimumab.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, immune therapy exhibited immune-related adverse events (irAEs) such as colitis, fatigue, rash, endocrine disturbance, and hepatotoxicity (128,129), which can be attributed to off-target effects of therapeutic drugs as well as dose-dependent toxicity. Relying on the precise regulation of the targeting properties of engineered bacteria, specific release of drugs at the tumor site can be achieved, which is beneficial to reduce the occurrence of adverse reactions related to immunotherapy.…”
Section: Perspectives and Prospectsmentioning
confidence: 99%